1998
DOI: 10.1562/0031-8655(1998)068<0296:wdpcso>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-dependent Photoacoustic Calorimetry Study of Melanin

Abstract: Photoacoustic calorimetry is used to examine the energy dissipation in melanin under physiological conditions (pH 7.2) following irradiation by UV and visible (VIS) light. Four different excitation wavelengths were examined: 264 nm, representative of UVC radiation, 351 nm and 400 nm (UVA-I radiation) and 527 nm, representative of VIS radiation. Following absorption at 527 nm, essentially all of the photon energy is released nonradiatively on a sub-nanosecond of excitation. Similar results are observed at 400 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
3
17
0
1
Order By: Relevance
“…Second, the remainder of each spectrum is broad and smooth, decreasing toward lower energies. We have previously shown that scattering has negligible contribution to the absorption spectrum for bulk eumelanin above 400 nm (22). In addition, scattering contributes no more than 15% to the total light extinction by samples separated by aggregation state at 350 nm (1).…”
Section: Resultsmentioning
confidence: 97%
“…Second, the remainder of each spectrum is broad and smooth, decreasing toward lower energies. We have previously shown that scattering has negligible contribution to the absorption spectrum for bulk eumelanin above 400 nm (22). In addition, scattering contributes no more than 15% to the total light extinction by samples separated by aggregation state at 350 nm (1).…”
Section: Resultsmentioning
confidence: 97%
“…1000 < MW < 3000, MW > 10 000) exhibit increased absorption at longer wavelengths, and whether these fractions are aggregates of the oligomers present in the MW < 1000 solution or longer oligomers remains to be determined. Photoacoustic calorimetry revealed the MW < 1000 sample is the only mass fraction showing measurable energy storage following UV‐A excitation (71). These data suggest unaggregated oligomers underlie the phototoxic effects of melanin and aggregation mitigates such processes.…”
Section: Aggregation Affects Photogeneration Of Reactive Oxygen Specimentioning
confidence: 99%
“…Furthermore, the low quantum yield for oxygen activation (10 −4 –10 −3 depending on the aggregation) suggests that the dominant process is likely rapid relaxation to the ground electronic state of the pigment (46). Such a conclusion is supported by photoacoustic studies of melanins (71), but the time resolution of this technique only reveals that non‐radiative relaxation occurs on the sub‐nanosecond time scale.…”
Section: Probing Non‐radiative Relaxation Of Eumelanins By Time‐resolmentioning
confidence: 99%
“…Dihydroxyacetone (DHA) † is commonly used in skin lotions to induce a self-tanning effect in human skin (1)(2)(3)(4)(5). The tanning effect is recorded by measuring the change in light absorption with time in human skin.…”
Section: Introductionmentioning
confidence: 99%